The questionable benefit of pectus excavatum repair on cardiopulmonary function: a prospective study. (15th July 2021) - Del Frari, Barbara; Blank, Cornelia; Sigl, Stephan; Schwabegger, Anton H; Gassner, Eva; Morawetz, David; Schobersberger, Wolfgang
Abstract:  : OBJECTIVES: Since the introduction of the minimally invasive technique for repair of pectus excavatum (MIRPE), increasing numbers of patients are presenting for surgery. However, controversy remains regarding cardiopulmonary outcomes of surgical repair. Therefore, the aim of our prospective study was to investigate cardiopulmonary function, at rest and during exercise before surgery, first after MIRPE and then after pectus bar removal. METHODS: Forty-seven patients were enrolled in a prospective, open-label, single-arm, single-centre clinical trial (Impact of Surgical Treatments of Thoracic Deformation on Cardiopulmonary Function) [NCT02163265] between July 2013 and November 2019. All patients underwent a modified MIRPE technique for surgical correction of pectus excavatum (PE), called Minor Open Videoendoscopically Assisted Repair of Pectus Excavatum. The patients underwent pre- and postoperative chest X-ray, three-dimensional volume-rendering computer tomography thorax imaging, cardiopulmonary function tests at rest and during stepwise cycle spiroergometry (sitting and supine position) and Doppler echocardiography. Daily physical activity questionnaires were also completed. RESULTS: The study was completed by 19 patients (15 males, 4 females), aged 13.9–19.6 years at the time of surgery. The surgical patient follow-up was 5.7 ± 7.9 months after pectus bar removal. No significant differences in cardiopulmonary and exercise parameters were seen after placement of the intrathoracic bar, or after pectus bar removal, compared to presurgery. CONCLUSIONS: Our findings indicate that surgical correction of PE does not impair cardiopulmonary function at rest or during exercise. Therefore, no adverse effects on exercise performance should be expected from surgical treatment of PE via the modified MIRPE technique. Clinical trial registration number: clinicaltrials.gov [ClinicalTrials.gov number, NCT02163265]. Abstract : Pectus excavatum (PE) is the most common congenital anterior chest wall deformity, with a reported incidence of 0.1–0.3%.